(untitled) (Marketing Journal, 2026)
n this article, the role and impact of the service sector on the sustainable development of the regional economy have been analyzed. The service sector has been substantiated as an important factor in the formation of gross regional product, employment gro wth, and the enhancement of regional competitiveness. Strategic, institutional, innovative, and territorial approaches to service sector development have been examined. Based on the results obtained, it has been shown that sustainable economic growth of th e region can be achieved through digital transformation, infrastructure development, and the strengthening of human capital in the service sector. № 1 -SON YANVA R, 202 6-YIL 265